Clinical application of butylphthalide sequential therapy on PTX-3, S100B, IL-6 in acute cerebral infarction : PTX-3, S100B, IL-6 in acute cerebral infarction - Meng, Pin; Zhang, Jianyu; Li, Jiaojiao; Ji, Niu; Zhou, Xinyu; Xu, Bingchao (Journal of Medical Biochemistry, 2025)
.
Keywords: .